Competition Among Pharmacies as a Determinant of Drug Expenditures - Zixuan Peng PhD; Audrey Laporte PhD; Xiaolin Wei PhD; Peter C. Coyte PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
This study explored and compared the associations between pharmacy competition and drug expenditures by individuals with influenza. This study used a dataset consisting of 6 694 534 individuals who purchased drugs for influenza at pharmacies from 2015 to 2019 in China. Patients’ annual average influenza-specific drug expenditures per visit at pharmacies was the outcome variable of interest. Pharmacy competition was measured using the Herfindahl-Hirschman index. A 3-way fixed-effects model combined with a lagged identification strategy was constructed to estimate the association between pharmacy competition and drug expenditures. When the radius of the market was set to 1, 5, and 10 km, for each 10% increase in the degree of total competition in the market, an individual’s annual average influenza-specific drug expenditures per visit fell by 0.65%, 2.21%, and 5.20%, respectively. With a more detailed understanding of the underlying mechanism through which pharmacy competition affects the behaviors of health care providers, competition can be considered as a potential tool to assist decision makers in the design of policies to curtail the growth in drug expenditures.